A scheme (Diff NEMO) for enhancing QoS in network mobility - Hussein, Loay Faisal; Hassan Abdalla Hashim, Aisha; Habaebi, Mohamed Hadi; Hassan, Wan Haslina (Asian Network for Scientific Information, 2015)
Network mobility basic support protocol (RFC 3963) is a novel thought for handling a bunch of nodes within a moving vehicular area. Namely, this protocol upholds continuous internet connectivity to nodes by establishing a bi-directional tunnel between Mobile Router (MR) and Home Agent (HA), when the MR of a mobile network changes its point of attachment. The bi-directional tunnel is set up as soon as the mobile router sends a successful Binding Update (BU) to its HA in order to inform the home agent about its current point of attachment. All traffic flow between the nodes in the mobile network and correspondent node must pass through the HA. This leads to sub-optimal routing that can surely disrupt and deteriorate all communications to and from the Mobile Network Nodes (MNN). Even the overheads can be further amplified if mobile networks are nested which is unacceptable for real-time applications that require certain Quality of Service (QoS) restrictions. Therefore, this study endeavors to propose a new scheme that bypasses the HA to cater optimal path and take the advantage of DiffServ to enhance QoS in the network mobility. The performance of the proposed scheme has been evaluated by using Network Simulator (NS-2). Subsequently, it benchmarked with the standard NEMO BSP that was proposed by Internet Engineering Task Force (IETF). The obtained results show that the proposed scheme outperforms the standard NEMO BSP in terms of packets loss rate and the probability of dropping BU.